Early prediction of adverse outcomes in infants with acute bilirubin encephalopathy. Issue 7 (4th June 2020) - Kang, Wenqing; Yuan, Xiao; Zhang, Yaodong; Song, Juan; Xu, Falin; Liu, Dapeng; Li, Rui; Xu, Bangli; Li, Wen; Cheng, Yanchao; Zhu, Changlian
Abstract: Objective: Acute bilirubin encephalopathy (ABE) remains one of the important causes of neonatal mortality and child disability, early identification, and intervention which could improve outcomes. The purpose of this study was to evaluate early predictors of adverse outcomes in infants with ABE. Methods: Newborns of gestational age ≥ 35 weeks and diagnosed with ABE were included in the study. Bilirubin‐induced neurological dysfunction (BIND) score, total serum bilirubin (TSB) peak value, and serum albumin levels were determined. Adverse outcomes were defined as death or survival with auditory dysfunction and/or cerebral palsy. Results: Eighty‐two infants were eligible for recruitment in the study. The outcome data from 76 ABE infants (92%) were used for analysis, of which 25 infants got adverse outcomes and 51 live a normal life. Univariate analysis for BIND score, TSB peak value, bilirubin–albumin ratio (B/A), albumin level, abnormal AABR, and neonatal sepsis was performed to elucidate the association with adverse outcomes. Bivariate logistic regression analysis showed B/A (OR 10.48, 95%CI: 1.55–70.81, P  = 0.02) and BIND score (OR 3.68, 95%CI: 1.39–9.72, P  = 0.01) were correlated with adverse outcomes. ROC curve analysis showed that B/A (≥8.9 mg/g), BIND score (≥6) could predict adverse outcomes of ABE separately; B/A in conjunction with BIND score could increase prediction sensitivity to 100%. Interpretation: Both B/A and BIND score can be used to predict adverse outcomes of ABE, and the combination of the two parameters can increase prediction sensitivity significantly.